1988
DOI: 10.1002/ddr.430150203
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐specific behavioral, cognitive, and in vivo changes in community residing subjects with age‐associated memory impairment and primary degenerative dementia of the Alzheimer type

Abstract: Stage-specific relationships between the seven-stage Global Deterioration Scale (GDS) for age-associated memory impairment and primary degenerative dementia of the Alzheimer's type and behavioral, cognitive, and neuroradiologic changes were examined in community residing subjects with normal aging or Alzheimer's disease (AD). The results revealed significant decrements between GDS stages 2 and 3; 3 and 4; 4 and 5; and 5 and 6 for most behavioral measures. No decrements were noted between GDS stages 1 and 2. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
5

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 27 publications
1
107
0
5
Order By: Relevance
“…Recently, the task of predicting conversion from MCI to AD has received a lot of attention, mainly because, nowadays, large multi-center studies, such as the ADNI, provide longitudinal data to the research community. The MCI term was first introduced in the literature by Reisberg et al [120] in 1988 and two decades later, Farias et al [121] showed that a 10%-15% rate of MCI subjects will progress to dementia. The biggest challenge in AD assessment is to predict if a patient will develop the disease.…”
Section: E Quantitative Mri Studies Based On Texture Analysismentioning
confidence: 99%
“…Recently, the task of predicting conversion from MCI to AD has received a lot of attention, mainly because, nowadays, large multi-center studies, such as the ADNI, provide longitudinal data to the research community. The MCI term was first introduced in the literature by Reisberg et al [120] in 1988 and two decades later, Farias et al [121] showed that a 10%-15% rate of MCI subjects will progress to dementia. The biggest challenge in AD assessment is to predict if a patient will develop the disease.…”
Section: E Quantitative Mri Studies Based On Texture Analysismentioning
confidence: 99%
“…Using this staging procedure, control subjects are assigned to GDS stage 1 and have neither subjective nor objective evidence for cognitive impairment, subjects at GDS stage 2 have subjective cognitive deficits in the absence of objective impairment, subjects at GDS stage 3 have objective evidence of memory deficit sufficient to interfere with performance in demanding employment and social settings, and subjects at GDS stages 4 to 7 have clear evidence of cognitive deficit comparable with mild (GDS=4), moderate (GDS=5), and moderately severe (GDS=6) AD. Stage specific relationships between GDS level assignments and scores on mental status, psychometric, and neuro-imaging measures have been reported [30] and current data on the validity and reliability of this staging procedure has been reviewed [31] .…”
Section: Data Collection In New Yorkmentioning
confidence: 99%
“…The concept of MCI was introduced by the end of the previous century 24 and since then has been recognized as a common condition in old age. However, considerable debate has emerged regarding its definition and assessment criteria.…”
Section: Definition and Epidemiologymentioning
confidence: 99%